Happiness and hardship : opportunity and insecurity in new market economies - Graham, Carol, 1962- (Brookings Institution Press, 2002)
Subjective well being, or happiness, has been analyzed in detail by psychologists for decades. Yet only recently has it become the subject of economic analysis. In Happiness and Hardship, Carol Graham and Stefano Pettinato provide a new conceptual framework for analyzing the relationship between subjective well being and the political sustainability of market-oriented economic growth in 17 Latin American countries and Russia. Several variables#x97;such as marital status, employment, and inflation#x97;are known to influence happiness. Graham and Pettinato have identified other variables that have impor.
Keywords: Income distribution -- Psychological aspects.; Economic development -- Psychological aspects.; Happiness.; Income distribution -- Latin America -- Psychological aspects.; Happiness; Revenu -- Répartition -- Aspect psychologique.; Développement économique -- Aspect psychologique.; Bonheur.; Revenu -- Répartition -- Amérique latine -- Aspect psychologique.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic development -- Psychological aspects; Latin America